Систематика хитонов рода Spongioradsia Pilsbry, 1893 (Ischnochitonina, Ischnochitonidae) - Сиренко, Б.И. (Вестник зоологии, 1976)
The article deals with a specification of the Spongioradsia genus and a description of two species S. aleutica (Dall, 1879) and S. subaleutica S i r e n k o sp. n. inhabiting the seas of the USSR.